PENGARUH SUHU PENYIMPANAN DAN JENIS KEMASAN TERHADAP MUTU ABON IKAN TERBANG - Antri Jayadi; Badaruddin Anwar; Andi Sukainah (Universitas Negeri Makassar, 2016)
This study aimed to determine changes in the quality shredded flying fish are packed with aluminum foil and polyethylene were stored at 28 0 C and 10 0 C. The design used in the study is completely randomized factorial design (RAL Factorial).Parameters measured were free fatty acid content and moisture content.Data analysis technique used is the analysis of variance using SPSS version 21.The results of the study to the lowest levels of free fatty acids at room temperature storage is polyethylene packaging while at cold temperature storage is aluminum foil packaging.The test results showed that the content of the water content of the lowest water levels in the storage room temperature or cold temperature is polyethylene packaging